The gender of “cleis”: correct spelling of Chiasmocleis supercilialbus Morales and McDiarmid, 2009, and Elachistocleis magnus Toledo, 2010 (Anura, Microhylidae) - Peloso, Pedro L.v.; Mcdiarmid, Roy W.; Caramaschi, Ulisses (Zootaxa, 2013)
Morales and McDiarmid (2009) and Toledo (2010) described and named, respectively, Chiasmocleis supercilialbus and Elachistocleis magnus. We argue that the specific epithets of both names are discordant with the gender of their respective genera and need correction.